Healthy Life Trajectories Initiative: Summary of the evidence base for pregnancy‐related interventions to prevent overweight and obesity in children. (16th August 2019) - Grobler, Liesl; Visser, Marianne; Siegfried, Nandi
Summary: This overview of systematic reviews (SRs) aimed to identify dietary and lifestyle interventions in pregnant women that reduce the prevalence of overweight, obesity, and/or risk factors thereof, in their children. Following identification of eligible SRs, a matrix of all included studies identified overlap between SRs. The most recent, comprehensive, high‐quality SRs were selected for further dissagregation. We developed a Grading of Recommendations, Assessment, Development and Evaluations (GRADE)‐based effectiveness matrix incorporating effect size and study quality to prioritise interventions as (1) beneficial or harmful, (2) possibly beneficial or possibly harmful, (3) no effect, (4) possibly no effect, or (5) uncertain effect. Of the 27 SRs identified, 16 SRs were excluded due to overlap. From 11 remaining SRs, five discrete interventions were ranked "beneficial" or "possibly beneficial" for reducing risk factors for childhood obesity: (1) balanced energy/protein supplements, (2) dietary counseling alone, (3) low glycemic index dietary advice, (4) diet and exercise counseling, (5) diet counseling and supervised exercise. High protein supplementation was ranked "harmful" as it increased the risk of small‐for‐gestational age (SGA) infants in normal‐weight pregnant women. Evidence of the impact of pregnancy‐related diet or lifestyle interventions, on childhood obesity was limited. Five dietary interventions, alone or in combination with exercise, showed beneficial effects on the risk factors for childhood obesity.